2013
DOI: 10.1093/qjmed/hct210
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden in inpatient relatives: the forgotten side of medical management

Abstract: The prevalence of symptoms of anxiety and depression in family members remains high at the end of acute health care. It is hoped that improving the provision of information will decrease the risk of psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 19 publications
4
22
0
4
Order By: Relevance
“…2CFurther research is needed to identify the most effective and cost-effective ways to implement routine family conferences in the ICU setting. Numerous observational studies have suggested the need for improved communication with family members (137,(162)(163)(164)(165)(166)(167). One multicenter observational study analyzed recordings of 51 family conferences and published results in a series of articles (151)(152)(153).…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…2CFurther research is needed to identify the most effective and cost-effective ways to implement routine family conferences in the ICU setting. Numerous observational studies have suggested the need for improved communication with family members (137,(162)(163)(164)(165)(166)(167). One multicenter observational study analyzed recordings of 51 family conferences and published results in a series of articles (151)(152)(153).…”
Section: Recommendationmentioning
confidence: 99%
“…Ample evidence exists describing the importance that patients and families place on high-quality communication in the ICU (26,27,170,171). Furthermore, additional evidence demonstrates that poor communication can cause patient and family dissatisfaction (162)(163)(164)(165) and even harm in the form of anxiety, depression, symptoms of PTSD and complicated grief (137,166,167,172). Given the importance of high-quality staff-family communication to familycentered outcomes, many investigators have examined communication training programs as an intervention to improve the quality of communication in the ICU setting.…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar da multiplicidade de aspectos que são afetados na vida cotidiana dos cuidadores familiares estes são considerados o "lado esquecido" durante todo o período de internação hospitalar [29][30] . Nesse sentido, a enfermagem exerce papel fundamental na avaliação e manejo do stress, estado de saúde e sentimento de esperança dos cuidadores familiares 31 .…”
Section: Discussionunclassified
“…Fehlende Information kann zu Schlafstö-rungen, Angst und Stress führen [2][3][4][5][6][7]. Etwa 50 % der Angehörigen suchen im Internet nach Informationen [8].…”
Section: Hintergrund Und Fragestellungunclassified